TranExamic Atomized for Pediatric post-Operative Tonsillectomy hemorrhage (TEAPOT): Study protocol for a pilot randomized controlled trial - Andrew D. Meyer; Whitney Schwarz; Dylan Erwin; Marisa Earley; Venkata K. Yellepeddi; Thomas H. Chun; T. Charles Casper; Daniel K. Nishijima (PLoS ONE, 2026)
Tonsillectomy is the second most common performed surgical procedure in children in the United States. Unfortunately, up to five percent of children return to emergency departments (ED) for post-tonsillectomy hemorrhage (PTH). To control PTH, most pediatric otolaryngologists return to the operating room (OR) for cauterization of the bleeding source. Retrospective studies suggest that nebulized tranexamic acid (TXA), an antifibrinolytic agent, can reduce the severity of post-tonsillectomy hemorrhage (PTH), however, its efficacy and safety have not yet been tested in randomized controlled trials. We designed the TranExamic Atomized for Pediatric post-Operative Tonsillectomy hemorrhage (TEAPOT) trial protocol to evaluate the feasibility of conducting a confirmatory clinical trial to evaluate the effects of TXA in children with PTH. We will randomize children presenting to the ED with secondary PTH to receive three 5-mL nebulized doses of either TXA (TXA 100 mg/ml) or placebo (normal saline). The following outcomes will be measured: feasibility (number of enrolled patients per site per year); protocol adherence (receipt of at least two nebulization doses); return to the operating room; pain reported on the FACES scale; parent and child anxiety assessed by the Patient-Reported Outcomes Measurement Information System (PROMIS) Anxiety measure; systemic and local (pharmacokinetic model derived) concentrations of nebulized TXA; coagulation biomarkers; and adverse events, including bleeding, thrombosis, and seizures. Our multicenter trial will provide important preliminary data on the feasibility and pharmacokinetics of nebulized TXA in preparation for a definitive clinical trial of children with secondary post-tonsillectomy hemorrhage. Registered at ClinicalTrials.gov ID# (NCT07565753) on May 4 th , 2026, https://clinicaltrials.gov/study/NCT07565753?term=teapot&viewType=Card&rank=1